Entrepreneurship, gender gap and developing economies: the case of post-apartheid South Africa. (4th July 2018) - Nyakudya, Frederick Wedzerai; Simba, Amon; Herrington, Michael
Abstract : This empirical study examines the extent to which risk aversion and entrepreneurial ability influence an individual's decision to enter into entrepreneurship. Precisely, it delineates the gender gap in self-employment, nascent and high growth entrepreneurship. In doing so, it utilizes the Global Entrepreneurship Monitor South Africa databases containing 19, 469 usable cases sampled between 2009 and 2014. The study adopts a quantitative approach and it applies an estimator in the form of a probit model and a non-linear decomposition technique to test established hypotheses. The results indicate that lower levels of knowledge and skills among women explain a substantial part of the gender gap. Thus, the gender gap in nascent and high growth entrepreneurship would be reduced if women had similar characteristics as men. Also, their entry rates into self-employment would be high and there would be no gender difference. This shifts the emphasis from the significance of risk aversion for local entrepreneurship to accentuate the importance of entrepreneurial-specific skills required to successfully engage in entrepreneurship.